Kemitraan Gender Dalam Konsep Ketahanan Keluarga Perspektif KHI Dan Implementasinya Pada Keluarga Muslim Karo Di Kecamatan Stm Hilir, Deli Serdang - Khaidir, Ainul Mardhiyah; Radwan Siddik Turnip, Ibnu (UNES Law Review, 2023)
This article aims to find out the perspective of the Compilation of Islamic Law (KHI) regarding gender partnerships in the concept of family resilience, and how it is implemented in Karo Muslim families in STM Hilir District. This research is empirical juridical research using a legal science and legal sociology approach (legal sociology approach), using primary and secondary data sources. Primary data sources were obtained from interviews with a number of informants who are members of the Karo Muslim community in STM Hilir District, while secondary data sources were obtained from primary legal materials such as Law No. 1 of 1974 concerning marriage, the Compilation of Islamic Law (KHI), and the book of fiqh. The data analysis method used is a qualitative method. The research results show that. Gender partnership is one of the variables in the concept of family resilience which has four indicators, namely aspects of togetherness in the family, husband-wife partnership, openness in financial management, and family decision making. From the perspective of the Compilation of Islamic Law (KHI), although the article does not specifically regulate gender partnerships, the indicators can be found in several articles in the KHI which support the realization of gender partnerships in family life. In its implementation, from 10 informants from the Karo Muslim community in STM Hilir District, it was discovered that indicators of openness in family financial management were implemented well, where husband and wife were directly involved in managing family finances together and transparently. Meanwhile, explaining other indicators still needs to be improved so that the values ​​of gender partnership as regulated in the KHI can be implemented well in Karo Muslim families, STM Hilir District.